An Experiment in the Earth Physics Leaning: Sunlight Observation for Determining Radius of The Earth - Nur Islami (Journal of Educational Sciences, 2020)
In the learning of the earth physics, sometime students got comfusing due to they cannot imagine how to determine the physical property of the earth such as, its mass, its volume and its diameter. This study was focused on how to use the sunlight for degermation of the earth radius through the simple experiment. In this study, an accurate and simple method have been introduced to the student on how to measure the earth radius. The experiment just used a camera and then the student started to determine the earth radius. In the end of the experiment student can explain how the sunlight can be used to determine the earth radius mathematically. They found that the radius of the earth is about 6243.04 km with a standard deviation of 13.70 km. The average results that is obtained by student is actually within 1.9% of the real value of the earth radius which is at 6371 km. This study shows that the real experiment is definitely able to show the real experience on how to determine the earth radius.